One-carbon homologation of alkenes - Marcus C. Grocott; Matthew J. Gaunt (Nature, 2025)
Abstract One-carbon homologues are structurally related and functionally identical organic molecules whose chain lengths differ by a single methylene (–CH 2 –) unit 1 . Across many classes of molecule—including pharmaceutical agents, natural products, agrochemicals, fragrances and petroleum products—the physicochemical characteristics exhibited by members of a homologous series subtly differ from one compound to another, which can impart remarkable differences to their function 2 . The efficient generation of homologues is, therefore, an important strategy in molecular discovery programmes 3,4 . Despite the availability of homologation strategies for several functional groups 5,6 , direct and general methods for one-carbon chain extension in alkenes remain an unmet synthetic need 7,8 . Here we report a catalytic one-carbon homologation process that is effective for many classes of alkene in simple and complex molecules. By leveraging the intrinsic reactivity of a new multifaceted allylsulfone reagent, a streamlined one-pot process, involving cross-metathesis and a fragmentation–retro-ene cascade, formally inserts a single methylene unit into the alkene chain. Among the applications of this process to several structurally and functionally complex molecules, we demonstrate how this practical transformation generates previously unexplored homologues of cyclosporine A 9 . These homologues exhibit modulated pharmacological and biological properties and could provide promising leads as cyclophilin inhibitors, a target that has great potential in many disease areas 10 .